PEMANFAATAN MEDIA SMARTPHONE DALAM MENGEMBANGKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Pribadi, Chiquita Azura; Yantoro, Yantoro; Noviyanti, Silvina (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the use of smartphones as a medium to develop students' learning interest in IPAS (Science and Social Studies Integration) learning in elementary schools. The research was conducted using a descriptive method with the subjects being fifth-grade students at SD Negeri 28/IV Jambi City during the odd semester of the 2024/2025 academic year. Research data were obtained through observation, interviews, and documentation. The data analysis technique employed was interactive analysis, consisting of data collection, verification, and conclusion drawing. The findings indicate that the use of smartphones in learning was implemented in stages: (1) identifying key activities, (2) determining the sequence, (3) allocating time and resources, and (4) implementation. The use of smartphones in the implementation stage brought benefits for both teachers and students teachers became more creative and innovative, student attention and interest increased, understanding was enhanced, learning objectives were achieved, and a more enjoyable learning environment was created. Furthermore, the use of smartphones had both positive and negative impacts. Based on the results, it was concluded that the school community was able to maintain the effective use of smartphones in learning. It is hoped that the findings of this study will be useful for future research.